Boron carbide morphology changing under purification; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Rakhmatullin I. A. Ilyas Aminovich (Materials and technologies new generations, 2015)
Title screen